ANALYSIS OF THERMAL TRANSFER VALUES IN TEACHING CLASSROOMS - Tri Wulan Sari; Dyah Nurwidyaningrum; Jonathan Saputra; Denny Yatmadi; Sujito Sujito (UPT Publication and Journal Management, Islamic University of Kalimantan, 2024)
Erratic weather, such as intense heat followed by heavy rain, is causing air pollution in the sky of Jakarta. According to the SNI 03-6389-2011, which deals with energy conservation in building envelopes, the overall thermal transfer value (OTTV) for walls should not exceed 35 W/m2. This study aims to analyze OTTV in Class T and Class S. Class S uses clear glass, while Class T has a shading device in the form of a sunglass sticker. The method used involves calculating the total outer wall area, glass area, window-to-wall ratio (WWR), solar factor value, and then obtaining the OTTV. The results of the study show that the WWR value for Class T was 0.5, while for Class S it was 0.4. The OTTV value in Class T is 58.74 W/m2, whereas the OTTV in Class S is 70.64 W/m2. Despite both classrooms not meeting the SNI requirements, the classrooms using shading devices have OTTV values closer to the SNI standard.